(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The current examination was intended to distinguish obstruction in tip top sunflower genotypes against charcoal decay illness for assortment improvement program. Sixteen sunflower genotypes were chosen to check the illness seriousness of charcoal decay. It was uncovered that all the genotypes were powerless to charcoal decay infection. The genotype 14068 was profoundly defenseless against the infection with high decrease in yield be that as it may, genotypes 14013, 14052, 14082 and 14095 were safe against the sickness dependent on rating scale and brought about high return in parched area of Bahawalpur. Safe genotypes should be chosen in reproducing system to deliver new sunflower lines exceptionally safe against charcoal decay to take care of truly expanding populace of the world.